Management strategies for water use efficiency and micro irrigated crops : principles, practices, and performance - Goyal, Megh Raj; Pandian, B. J. (Toronto : Apple Academic Press, 2018)
Management Strategies for Water Use Efficiency and Micro Irrigated Crops presents new research and technologies for making better use of water resources for agricultural purposes. The chapters focus on better management to improve allocation and irrigation water efficiency and look at performance factors as well. Chapters look at irrigation technology, environmental conditions, and scheduling of water application. One section of the book focuses on water management in the cultivation of sugarcane, a very important industrial crop used in many fields. Other sections are devoted to principles and challenging technologies, water use efficiency for drip-irrigated crops, performance of fertigated rice under micro irrigation, and evaluation of performance of drip-irrigated crops. This valuable book is a must for those struggling to find ways to address the need to maintain efficient crop production in the midst of water shortages. With chapters from hands-on experts in the field, the book will be an invaluable reference and guide to effective micro irrigation methods.
OCLC-licensed vendor bibliographic record.
Keywords: Water in agriculture; Water-supply, Agricultural -- Management; Microirrigation -- Management; TECHNOLOGY & ENGINEERING / Agriculture / General; TECHNOLOGY / Agriculture / Crop Science; TECHNOLOGY / Agriculture / Irrigation; TECHNOLOGY / Agriculture / Soil Science